Plasma Medicine - Concepts and Clinical Applications - Yusuf Tutar; Lutfi Tutar (IntechOpen, 2018)
Plasma can be defined as the extracellular matrix of blood cells. Plasma components, their role in human health risk evaluation, and their functional and clinical analyses are covered in this book. Furthermore, physical plasma-ionized gas is one of the four fundamental states of matter. This homonym has begun to emerge because it can interact with living systems. The physical plasma biomedical applications are reviewed in drug delivery and wound healing medical applications. This approach revolutionizes the therapeutic approaches in medicine and may open up new concepts and clinical applications. The book is an essential source for researchers in the field and provides a platform for different professions.
English
Keywords: Medicine; Internal Medicine; Health Sciences